Cerebrolysin in Patients Diagnosed with Subarachnoid Hemorrhage—The Results of an Observational Cohort Study - Klaudyna Kojder; Konrad Jarosz; Agata Andrzejewska; Joanna Solek-Pastuszka; Karolina Skonieczna-Żydecka; Mariusz Kaczmarczyk; Anna Jurczak (Biomedicines)
Background: Subarachnoid hemorrhage (SAH) is associated with high mortality and a high level of disability. Progress in surgical and endovascular techniques has lowered the mortality rate in patients with SAH. However, many patients are left with neurological impairment. Objectives: In our study we wanted to examine the impact of Cerebrolysin on treatment results in patients with SAH diagnosis. Methods: The data of 47 patients, divided into Cerebrolysin (26) and non-Cerebrolysin (21) group were included. We examined the correlation between Cerebrolysin administration and additional Amantadine treatment or neuromonitoring, craniectomy, and endovascular treatment and its impact on the Glasgow Outcome Scale (GOS) score, length of stay (LOS), and mortality. Results: Our study shows that Cerebrolysin improves the mortality rate in combination with neuromonitoring in a group of patients with severe SAH. It does not affect the raw values of GOS or LOS in patients with SAH. Conclusions: Further studies with larger patient groups are needed to investigate the role of Cerebrolysin as an additional treatment in SAH.